Oxford international primary English student book for grade 3 - Barber, Alison (Karachi : Oxford university press, 2022)
"Oxford International Lower Primary English Student Book (Grade 3)" is a comprehensive and engaging English textbook designed for Grade 3 students. The book is part of an international curriculum and focuses on developing core English language skills such as reading, writing, speaking, listening, grammar, and vocabulary. It uses interactive and child-friendly content to build a strong foundation in English at an early stage.
Keywords: English : Textbook; Oxford : Grade 3